Translation Loss and Gain in the Translation of Nias Cultural Jewelry Terms into English : Penelitian - Afore Tahir Harefa; Theresia Trines Anjelin Zai; Elnardus Fransiskus Jafrinus Namo; Yofita Gulo (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aimed to investigate translation loss and gain in the translation of Nias cultural jewelry terms into Indonesian and English. A qualitative research design was employed, using museum books and catalogues from Museum Pusaka Nias as data sources. Data were analyzed through descriptive and comparative qualitative methods to identify instances of loss and gain in both target languages. The results revealed nine instances of gain, mostly involving the addition of descriptive words such as "golden," "silver," "ivory," or "battle" to clarify meaning for non-Nias readers. Loss occurred in five cases, primarily due to omissions of gender, cultural specificity, or symbolic elements, such as the absence of the word "durian" in English translations. The study highlights the challenges of cross-linguistic and cross-cultural translation and emphasizes the importance of balancing accessibility and cultural fidelity in translating heritage terms